1992
DOI: 10.1002/ijc.2910520612
|View full text |Cite
|
Sign up to set email alerts
|

DOK, a cell line established from human dysplastic oral mucosa, shows a partially transformed non‐malignant phenotype

Abstract: There are many reports of cell lines being established from human oral squamous-cell carcinomas but apparently none of cell lines from dysplastic or "pre-malignant" oral mucosa. We describe here the isolation and characterization of a cell line, DOK (dysplastic oral keratinocyte), from a piece of dorsal tongue showing epithelial dysplasia. The tissue was obtained from a 57-year-old man who was a heavy smoker prior to the appearance of a white patch on his tongue. Eleven years later a squamous-cell carcinoma de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 21 publications
(9 reference statements)
0
95
0
Order By: Relevance
“…However, we did not detect ␥2 expression in normal or premalignant tissue specimens, and it is perhaps more likely that DOK cells are indeed carcinoma cells as they were derived from epithelium immediately adjacent to an invasive HNSCC and harbor a mutation within p53. 30 In a previous study, 34 we reported that p53 mutations were absent in cells derived from premalignant oral lesions, implying that this is not an early event in HNSCC tumor development. Indeed, DOK cells show other features of a transformed phenotype compared to other premalignant cells, including aneuploidy, cellular immortality and a reduced serum and factor requirement for in vitro growth.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, we did not detect ␥2 expression in normal or premalignant tissue specimens, and it is perhaps more likely that DOK cells are indeed carcinoma cells as they were derived from epithelium immediately adjacent to an invasive HNSCC and harbor a mutation within p53. 30 In a previous study, 34 we reported that p53 mutations were absent in cells derived from premalignant oral lesions, implying that this is not an early event in HNSCC tumor development. Indeed, DOK cells show other features of a transformed phenotype compared to other premalignant cells, including aneuploidy, cellular immortality and a reduced serum and factor requirement for in vitro growth.…”
Section: Discussionmentioning
confidence: 82%
“…Human epithelial cell lines SCC25, 26 T45, 27 BICR16, 28 HN6, HN12, HN13, HN26 and HN30, 29 derived from HNSCC, and DOK, derived from a premalignant oral lesion, 30 were cultured in DMEM supplemented with 10% FBS and 0.4 g/ml hydrocortisone on a feeder layer of lethally irradiated Swiss-3T3 fibroblasts. Feeder cells were removed prior to subculturing or RNA preparation by standard procedures.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…23) obtained from European Collection of Cell Cultures were suspended in 50 mL of growth factor-reduced matrigel (BD Biosciences), and inoculated alone (n ¼ 6) or together with 10 5 fibroblasts of the strains NF5 (n ¼ 6), CAF1 (n ¼ 6), or CAF5 (n ¼ 6) subcutaneously on the back of 12-week-old nonobese diabetic/severe combined immunodeficient (NOD/SCID) IL2rg(null) mice (The Jackson Laboratory). Tumor incidence and development (volume) was assessed at every 3 days.…”
Section: Tumor Xenografting In Nod/scid Il2rg(null) Micementioning
confidence: 99%
“…Human Cell Lines and Culture Conditions SCC25 and OSC2 (OSCC), and DOK (dysplastic oral keratinocytes), and A818-6 (Human Pancreatic Adenocarcinoma) human cell lines have been published [15][16][17][18] and were initially obtained from American Type Culture Collection. The human oral keratinocyte (HOK) whole lysate was purchased from ScienCell TM Research Laboratories (cat.…”
Section: Discussionmentioning
confidence: 99%